Opuśc nawiasy i zredukuj wyrazy podobne.
b)-(4x-2y+7)-(x+4y-2)+(5x+y-4)=
c) (6a(do potegi 2)-a-2)-(2a(do potegi 2)-a)+(4a-2)+(a(do potegi2)-1)=
d) (m-3n+1)+(2m+n-1)-(3m-2n+2)=
e) (6,2-2,5ab+3b)-(4,8+3b-2,5ab)=
f) (1/5x-4y+1/2)+(4/5x+2y-1/4)-(3/4+y)

1/3 to są ułamki ;)

2

Odpowiedzi

2010-02-22T14:24:24+01:00
B)-4x+2y-7-x-4y+2+5x+y-4=y-9
c) 6a(do potegi 2)-a-2-(2a(do potegi 2)-a)+(4a-2)+(a(do potegi2)-1)=36a²-a-2 -4a²+a+4a-2+a²-1=33a²-4+4a
d) (m-3n+1)+(2m+n-1)-(3m-2n+2)=m-3n+1+2m+n+1-3m+2n-2=0
e) (6,2-2,5ab+3b)-(4,8+3b-2,5ab)=6,2-2,5ab+3b-4,8-3b+2,5ab= 1,4
f) (1/5x-4y+1/2)+(4/5x+2y-1/4)-(3/4+y)= ⅕x-4y+½+⅘x+2y-¼-¾-y= x-3y-½
1 5 1
2010-02-22T14:36:39+01:00
B)-(4x-2y+7)-(x+4y-2)+(5x+y-4)=-4x+2y-7-x-4y+2+5x+y-4=-5x+5x+3y-4y-11+2=-y-9
c) (6a²-a-2)-(2a²-a)+(4a-2)+(a²-1)=6a²-a-2-2a²+a+4a-2+a²-1=6a²-2a²+a²-a+a+4a-5=5a²+4a-5
d) (m-3n+1)+(2m+n-1)-(3m-2n+2)=m-3n+1+2m+n-1-3m+2n-2=m+2m-3m-3n+n+2n-2=-2
e) (6,2-2,5ab+3b)-(4,8+3b-2,5ab)=6,2-2,5ab+3b-4,8-3b+2,5ab=6,2-4,8+3b-3b-2,5ab+2,5ab=1,4
f) (1/5x-4y+1/2)+(4/5x+2y-1/4)-(3/4+y)=1/5x-4y+1/2+4/5x+2y-1/4-3/4-y=1/5x+4/5x+2/4-4/4-4y+2y-y=x-3y-1/2